The impact of environmentally-specific servant leadership on organizational green performance: The mediating role of green creativity - Hou, Hong; Gai, Ruizhi; An, Li (Frontiers in Psychology, 2023)
In recent years, the environmental problems caused by excessive carbon dioxide emissions have become increasingly prominent. Society has put forward higher demands on the green development of enterprises, and how to improve the green performance of enterprises so as to contribute to the natural environment has become a hot issue. Based on a social learning theory, this paper investigates the impact of environmentally-specific servant leadership on organizational green performance through the questionnaire survey and tests the mediating role of green creativity and the moderating role of power distance orientation. By analyzing 576 valid questionnaires, the results show that: environmentally-specific servant leadership has a positive influence on organizational green performance; green creativity plays a mediating role between environmentally-specific servant leadership and organizational green performance; power distance orientation plays a moderating role between environmentally-specific servant leadership and green creativity, specifically, the higher the power distance orientation, the more significant the influence of environmentally-specific servant leadership on employees’ green creativity. This paper enriches the research on environmentally-specific servant leadership and proposes a new perspective on how to improve green performance in organizations, which has certain theoretical and practical implications.